2017
DOI: 10.1002/adfm.201703273
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Dependence of Tunneling Electroresistance and Switching Stability in Organic Ferroelectric P(VDF‐TrFE)‐Based Tunnel Junctions

Abstract: Ferroelectric tunnel junctions (FTJs) are promising candidates for nonvolatile memories and memristor-based computing circuits. Thus far, most research has focused on FTJs with a perovskite oxide ferroelectric tunnel barrier. As the need for high-temperature epitaxial film growth challenges the technological application of such inorganic junctions, more easily processable organic ferroelectrics can serve as alternative if large tunneling electroresistance (TER) and good switching durability would persist. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 47 publications
(57 reference statements)
1
46
0
Order By: Relevance
“…The pioneering work by Chanthbouala et al demonstrated that the gradual switching of the ferroelectric domain and the resulting change of resistance states can ensure a memristor response in FTJs . Subsequently, several works have explored the possibility of FTJs as artificial synapses . Recently, Boyn et al realized unsupervised learning using FTJ based simulations …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pioneering work by Chanthbouala et al demonstrated that the gradual switching of the ferroelectric domain and the resulting change of resistance states can ensure a memristor response in FTJs . Subsequently, several works have explored the possibility of FTJs as artificial synapses . Recently, Boyn et al realized unsupervised learning using FTJ based simulations …”
mentioning
confidence: 99%
“…[21] Subsequently, several works have explored the possibility of FTJs as artificial synapses. [18,24,25] Recently, Boyn et al realized unsupervised learning using FTJ based simulations. [26] In this work, we demonstrate an artificial synapse with ultralow femtojoule energy consumption based on Pt/BaTiO 3 / Nb-doped SrTiO 3 FTJ devices.…”
mentioning
confidence: 99%
“…1(g)], more notably in the high resistance state, with a larger conductance for positive bias which turns the junction into accumulation. 32 A similar effect is present in Pt/BTO/LSMO, even though it is less evident because of the smaller depleted region associated with the larger carrier density (N c $ 10 21 cm À3 ) [ Fig. 1(d)].…”
mentioning
confidence: 77%
“…We note that this result is coherent with previous works on Pt/BTO/LSMO 20 and Pt/BTO/Nb:STO 17,31 FTJs, and this dependence has also been recently verified in devices where the same electrodes are used with an ultrathin organic ferroelectric. 32 Figures 1(f) and 1(i) show the capacitance of the two devices as a function of bias. For this measurement, an Agilent E4980 LCR meter has been used with a sinusoidal excitation of frequency f ¼ 100 kHz and amplitude V pp ¼ 200 mV.…”
mentioning
confidence: 99%
“…The resistance of the "memory" layer can be dynamically reconfigured by voltageor current-induced ion implantation, interfacial charge accumulation, and so on. Usually, the electrodes are metal or oxide, such as Ag, Au, Pt, Ta, Ir, Cu, ITO, and so on, which will affect the resistive switching behavior by their different work function, electron affinity, electrochemical energy, and so on [33,34]. For the "memory" layer, various kinds of materials have been used, including binary oxide, nitride, perovskite, low-dimensional materials, and organic materials [35][36][37][38][39][40][41][42][43][44][45].…”
Section: Optoelectronic Resistive Switching Materials and Devicesmentioning
confidence: 99%